Pengaruh Manipulasi Ploidi Terhadap Efektivitas Pertumbuhan dan Hasil Tanaman Labu Kuning (Cucurbita moschene Dutchene) - Reza Prakoso Dwi Julianto; I Made Indra Agastya; Wahyu Fikrinda (Universitas Trunojoyo Madura, 2023)
Pumpkin (Cucurbita moschene Duthene) is plant sources of food that has high nutrition content. Increasing the productivity of pumpkin can be done through programs, which is the ploidy manipulation technique, the technique using a mutagen, namely colchicine. Application of colchicine in the wrong dose and soaking time can be toxic to plants. The research aim to gain recommendations for the right concentration of colchicine immersion to increase the growth and yield of pumpkin plants. Research was done by using a split plot design with subplots with colchicine concentration and the main plots of local Malang pumpkin varieties. The research results that application of colchicine immersion in several local pumpkin varieties showed a significant relationship at fruit quantity parameter. Application of colchicine with 3 dose ppm on local pumpkin variety Malang 1 (P3V1) showed the highest average fruit quantity compared to other treatments, which was 4 pieces. Optimal concentration of colchicine to increase the yield of local pumpkin plants is with 3 dose ppm can be seen from the highest average value on several parameters among others fruit number, fruit weight, and fruit diameter, but not significantly different from the colchicine concentration of 2 ppm and 4 ppm. The colchicine concentration of 2 ppm showed the highest average value of the sex ratio parameter was 25.51%.